Nucleocytoplasmic Shuttling of Human Cytomegalovirus UL84 Is Essential for Virus Growth - Gao, Yang (American Society for Microbiology (ASM), 2010)
Human cytomegalovirus (HCMV) UL84 is a multifunctional protein that is the proposed initiator for lytic viral DNA synthesis. Recently it was shown that UL84 displays nucleocytoplasmic shuttling. The role of shuttling in lytic DNA replication and virus growth is unknown. We now show that expression of the nonshuttling UL84 mutant failed to complement oriLyt-dependent DNA replication in the transient assay under conditions where core replication and ancillary proteins were expressed under the control of their native promoters. However, constitutive expression of the core replication proteins, along with the nonshuttling UL84 mutant, resulted in efficient oriLyt amplification, suggesting that shuttling may contribute to the activity of one of the auxiliary replication proteins. A recombinant HCMV bacterial artificial chromosome plasmid (BACmid) expressing the nonshuttling UL84 mutant (NS84 BAC) was defective for production of infectious virus. Quantitative PCR showed that NS84 BAC had decreased accumulation of viral DNA in both cellular and supernatant samples. Analysis of the accumulation of select viral mRNAs showed no difference in total cellular mRNA accumulation for IE2, IRS1, TRS1, UL102, UL105, and UL75 in cells transfected with the NS84 BAC. However, examination of cytoplasmic RNA and subcellular localization of IRS1 revealed a decrease in IRS1 mRNA accumulation and displaced protein localization, strongly suggesting that UL84 facilitated the localization of IRS1 mRNA to the cytoplasm. RNA pulldown assays showed that UL84 interacted with IRS1 mRNA. These results indicate that nucleocytoplasmic shuttling is essential for virus growth and strongly suggest that UL84 is responsible for localization of at least one virus-encoded transcript, IRS1 mRNA.